PENGARUH DOSIS PUPUK FOSFOR DAN KONSENTRASI GIBERELIN PADA PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica oleraceea L.) - Rohman, Nur; Widiatmanta, Jeka (Universitas Islam Balitar, 2017)
The flower cabbage (Brassica oleraceea L.) is a type of vegetable plant belonging to the family of cabbage plants (Cruciferae). Flower cabbage often called